Conditions and opportunities of workplace teaching/learning of teachers of preschool educational institutions (the case of Lithuania) - Smilgienė, Jurgita; Masiliauskienė, Erika (Social Welfare: Interdisciplinary Approach, 2019)
The problematic of learning in the workplace in the context of the activity of the Lithuanian educational (especially preschool) institutions today is the part of the culture of school activity that is still not sufficiently being actualized. The article presents the results of the empirical research that describe the conditions and opportunities of workplace teaching/learning of the teachers of a preschool educational institution and highlights the essential interferences to such teaching/learning.
Keywords: preschool teacher’s teaching/learning; teaching/learning in the workplace; conditions and opportunities of workplace teaching/learning